Reframing Dark Patterns in Digital Marketing Through Maqashid Al-Shariah: Towards Consumer Cognitive Intelligence - Hidayati, Heny; Nurcholifah, Ita; Mustafa, Muhammad Fahmi (Tujjar International Journal of Islamic Economics Development, 2026)
Digital marketing has changed how consumers engage with information and make decisions. In practice, different digital platforms act not only as promotional media but also as a way of influencing user behavior through the persuasive design of interfaces. One phenomenon that has been receiving increasing attention is that of dark patterns, which are design strategies that deliberately exploit consumers' cognitive biases to guide certain decisions. This study aims to analyze the phenomenon of dark patterns from the perspective of maqashid syariah, especially in terms of the protection of reason (hifz al-‘aql) and the protection of wealth (hifz al-mal), and formulate the concept of “consumer cognitive intelligence” as a form of response to the manipulative practices in the digital environment. This study employs a qualitative approach using an integrative literature review design, limitedly combined with the principles of a systematic literature review in the literature search and selection process. The results indicate that dark patterns not only cause economic losses but also have the potential to distort consumers’ thought processes and their freedom to make decisions. On the other hand, this study emphasizes that consumer protection is not sufficient through regulation and business ethics alone but also requires strengthening individuals’ internal capacities. Therefore, this study proposes the concept of “consumer cognitive intelligence from a maqashid perspective” as the ability to recognize, evaluate, and respond to digital information critically, consciously, and ethically. This study is expected to expand the study of Islamic marketing in a digital context while contributing to the discourse on contemporary marketing ethics.